Multiple Logistics Regression Model, Dominant Factors Affecting Health Service Utilization for PBI Participants in Jambi City - Arnild Augina Mekarisce; Dwi Noerjoedianto; Adila Solida (Pusat Riset dan Inovasi Nasional, 2022)
Background : The coverage of BPJS Health membership has reached more than 80% of the total population, but the utilization rate of health services for PBI group participants is the lowest, one of which is in Jambi City. The purpose of this study was to determine the dominant factors that influence the utilization of health services for PBI participants in Jambi City. Method : An observational analytic study using a cross sectional design with a population of PBI BPJS Health participants in Jambi City. Calculation of the sample using the Lemeshow formula, as many as 106 samples with accidental random sampling technique. The research instrument used a questionnaire sheet, then the data was processed through data editing, data coding, data entry, data cleaning, and data processing, then analyzed by univariate, bivariate with chi-square test, and multivariate with multiple logistic regression test. Results : The results showed that the most dominant factor influencing the utilization of health services in Jambi City PBI participants was knowledge (OR=0.173). Conclusion : Health Service Providers are expected to increase socialization and education efforts to the public on the importance of utilizing health services (promotive, preventive, curative, rehabilitative) both directly and by maximizing the role of social media accounts of health facilities.